The Relationship between Public Policy and Democracy : Motor Vehicle Tax Amnesty Policy in West Java - Mila Yuniar; Risfa Siti Roiatul Muna; Faisal Mujahid; Muhamad Farissulkhoer (GoResearch - Research & Publishing House, 2024)
The motor vehicle tax amnesty initiative implemented in West Java during the governorship of Dedi Mulyadi constitutes a form of public policy intervention aimed at fostering taxpayer compliance by eliminating administrative sanctions and tax arrears. From the perspective of public policy and democracy, this policy gives rise to debates between short-term fiscal effectiveness and long-term implications for social justice, accountability, and potential moral hazard. The present study employs a dual methodological approach, integrating the tenets of tax compliance theory and the principles of fiscal justice within the context of a democratic system. The findings indicate that the efficacy of tax bleaching is not exclusively determined by fiscal incentives; rather, it is also contingent on the consistency of law enforcement, policy transparency, and public participation in the formulation process. Consequently, such policies should be regarded as a component of a democratic governance design that demands equal treatment for all citizens before the law and state fiscal policy. The ramifications of this policy underscore the significance of institutional reform, thereby ensuring that tax incentives do not serve merely as a fiscal expedient, but rather evolve into a catalyst for fostering public trust within the ambit of a just and participatory democratic state.